Agrologística, un enfoque hacia la productividad y competitividad de Colombia - Bran Serna, Elizabeth
It is clear that the context of the agricultural sector in Colombia presents a series of structuralproblems that affect the economic and therefore social development of the country, which does notallow it to compete efficiently in international markets that are increasingly demanding and dynamic.The importance of logistics is then highlighted as an essential factor of competitiveness anddevelopment of the Colombian agricultural sector, which allows the management of the variousactivities of the supply chain required for the supply of agricultural products, responding to marketdemand with greater productivity, taking advantage of the comparative advantages that are availableand transformed into competitive advantages. An approach to the concept of agrologistics as a factorof productivity and competitiveness for Colombia is then presented